An ethnobotanical study of medicinal plants used by tribal and native people of Madhupur forest area, Bangladesh - Awang, Khalijah; Islam, K.M.; Saha, S.; Mahmud, I.; Mohamad, K.; Uddin, S.J.; Rahman, M.M.; Shilpi, J.A. (Elsevier, 2014)
Ethnopharmacological relevance: Madhupur forest area, Tangail is one of early human settlements in Bangladesh. Having abode in the vicinity of the forest, a strong ethnobotanical practice has prevailed in this area since ancient time. Due to the rapid deforestation during the last few decades, many plants have already disappeared or are facing extinction. Thus we attempted to document the medicinal plant use of Madhupur forest area with a view to preserve the ethnobotanical knowledge and in order to protect the biodiversity of this area. Materials and methods: The fieldwork was conducted during a period of 1 year. Data was collected by interview, questionnaire, and group discussion with randomly selected informants including indigenous, tribal people, and Traditional Health Practitioners (THPs) living in the study area. Recorded plants are listed along with their indication, part used, form of preparation and use value (UV). Results were also analysed to determine informant consensus factor (ICF) and fidelity level (FL) of the plants on the basis of their use under various ailment categories. Results: The present study has documented 78 medicinal plant species from 45 families used for the treatment of at least 77 different major and minor ailments and conditions. Medicinal plant species were categorised as tree, shrub, tuber, herb, and climber. Leaves were found to be the most frequently used plant part while decoction is the major form of preparation. In most cases preparations are either administered orally or applied topically. Conclusion: The present study revealed that some of the well-known medicinal plants are used extensively demonstrating an effective ethnobotanical practice in the study area. Plants with high ICF and FL values can be subjected to bioassay guided investigation while plants which scored low UVs require bioactivity screening to justify their use for the reported ailment.